PROFESSIONAL COMPETENCE DEVELOPMENT OF FUTURE TEACHERS BASED ON AN INTEGRATIVE APPROACH - M.E. Khurramov (Bright Mind Publishing, 2025)
This article shows the issue of developing professional competence of future teachers based on an integrative approach. The importance of integration of sciences is given.
Keywords: Integration, competence, competence, integrative approach, professional, development, future teachers.